Properties and performance of wood adhesives / Ahmad Azwan Abdullah - Abdullah, Ahmad Azwan (2001)
Wood adhesive is one important element in wood-based processing industries. Most of wood based industries such particle boards, glulam, plywood, boat construction, and more use good wood adhesive. The adhesives like Urea-formaldehyde (UF), Phenol-Formaldehyde(PF), Melamine-Urea-Formaldehyde, Resorcinol Formaldehyde, Thermoplastic Adhesives, Polyvinyl Acetate, Elastomeric Adhesives and other. Each of adhesive could use for certain wood based product. This is because the strengthens for each wood-based products are differences. Also, the combinations in adhesive contents are differences. Other than that, pH, presence of extractive, relative humidity, also contribute wood based.